2000
DOI: 10.1111/0022-4146.00184
|View full text |Cite
|
Sign up to set email alerts
|

The Causes of Regional Variations in U.S. Poverty: A Cross‐County Analysis

Abstract: The persistence of poverty in the modern American economy, with rates of poverty in some areas approaching those of less advanced economies, remains a central concern among policy makers. Therefore, in this study we use U.S. county-level data to explore potential explanations for the observed regional variation in the rates of poverty. The use of counties allows examination of both nonmetropolitan area and metropolitan area poverty. Factors considered include those that relate to both area economic performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
100
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 22 publications
13
100
0
5
Order By: Relevance
“…Similar to other regional studies [Sloboda, 1999;Levernier et al, 2000;Fullerton, 2001], multicollinearity affects a subset of the slope coefficient t-statistics. Both of the t-statistics for the incomplete primary school and the completed elementary school regressors fail to meet the 5 percent significance criterion.…”
Section: Estimation Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Similar to other regional studies [Sloboda, 1999;Levernier et al, 2000;Fullerton, 2001], multicollinearity affects a subset of the slope coefficient t-statistics. Both of the t-statistics for the incomplete primary school and the completed elementary school regressors fail to meet the 5 percent significance criterion.…”
Section: Estimation Resultssupporting
confidence: 65%
“…Accordingly, much of the recent research on this topic has been conducted for regional and metropolitan economies [Sloboda, 1999;Levernier et al, 2000;Fullerton, 2001;Gottlieb and Fogarty, 2003]. Studies in this category often focus their efforts on lower income regions and use model simulations to illustrate the potential gains from policies designed to encourage higher enrollment and graduation rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We use a disequilibrium partial-adjustment poverty model similar to Levernier, Partridge, and Rickman (2000) and Partridge and Rickman (2005;2008a). The model assumes a county's current equilibrium poverty rate is a function of its characteristics, such as job growth and demographics.…”
Section: Modelmentioning
confidence: 99%
“…In addition, a strong FIRE sector helps to underwrite other forms of economic activity. Research has shown that the percentage of total employment in agriculture tends to be positively related to poverty (Albrecht, Albrecht, and Albrecht 2000;Levernier, Partridge, and Rickman 2000). This is due in part to the fact that agriculture tends to predominate in rural areas with less diversified economies, and is also characterized by particularly high rates of underemployment compared to other industries (Slack and Jensen 2004).…”
Section: Employment Structurementioning
confidence: 99%